A Reference Grammar of Kotiria (Wanano) - Stenzel, Kristine (Book collections on Project MUSE., 2013)
Published through the Recovering Languages and Literacies of the Americas initiative, supported by the Andrew W. Mellon Foundation. This is the first descriptive grammar of Kotiria (Wanano), a member of the Tukanoan language family spoken in the Vaupes River basin of Colombia and Brazil in the northwest Amazon rain forest. The Kotirias have lived in this remote region for more than seven hundred years and participate in the complex Vaupes social system characterized by longstanding linguistic and cultural interaction. The Kotirias remained relatively isolated from the dominant societies.